Genetic advances in craniosynostosis. Issue 5 (4th February 2017) - Lattanzi, Wanda; Barba, Marta; Di Pietro, Lorena; Boyadjiev, Simeon A.
Abstract : Craniosynostosis, the premature ossification of one or more skull sutures, is a clinically and genetically heterogeneous congenital anomaly affecting approximately one in 2, 500 live births. In most cases, it occurs as an isolated congenital anomaly, that is, nonsyndromic craniosynostosis (NCS), the genetic, and environmental causes of which remain largely unknown. Recent data suggest that, at least some of the midline NCS cases may be explained by two loci inheritance. In approximately 25–30% of patients, craniosynostosis presents as a feature of a genetic syndrome due to chromosomal defects or mutations in genes within interconnected signaling pathways. The aim of this review is to provide a detailed and comprehensive update on the genetic and environmental factors associated with NCS, integrating the scientific findings achieved during the last decade. Focus on the neurodevelopmental, imaging, and treatment aspects of NCS is also provided.